Reduction-controlled graphene oxide saturable absorbers and its effect on ultrashort Er-doped fibre laser - Ismail, Mohd Afiq (Wiley, 2021)
The authors controlled the reduction of three graphene oxide (GO) saturable absorber (SA) thin films by controlling the exposure time under a solar simulator and afterwards, incorporated them into an Er-doped fibre laser in order to investigate their effect on ultrashort pulse. The authors also hypothesized that the controlled reduction would result in a controlled absorption, and ultimately, a controlled modulation depth. A larger modulation depth would lead to stronger pulse shaping and shorter pulse duration. Sample A was left unreduced, whereas samples B and C were exposed for 15 and 30 min, respectively. Afterwards, their modulation depths were measured using twin-detector method and determined to be 0.69%, 1.2% and 1.94%, respectively. When used as an SA in an Er-doped fibre laser, the result showed pulse duration shortening; from 670 to 520 fs, as well as spectral broadening; from 4.22 to 6.73 nm. In addition, we also observed changes in repetition rate, output power and time-bandwidth product (TBP). The result of this paper shows the feasibility of controlling the modulation depth of a GO SA and conclusively shows the effect of modulation depth on ultrashort pulse.